Caraval - Garber, Stephanie (New York : Flatiron Books, 2017)
A long-desired invitation to Caraval, the annual audience-participation show, prods Tella and Scarlett to escape their powerful, cruel father, but upon arriving Tella is kidnapped as part of the game.
Keywords: Sisters -- Fiction; Performing arts -- Fiction; Games -- Fiction; Kidnapping -- Fiction; Fantasy